Financial mathematics, derivatives and structured products - Chan, Raymond H.; Guo, Y Ves ZY.; Lee, Spike T.; Li, Xun (Singapore Springer Nature, 2024)
This book introduces readers to the financial markets, derivatives, structured products and how the products are modelled and implemented by practitioners. In addition, it equips readers with the necessary knowledge of financial markets needed in order to work as product structurers, traders, sales or risk managers. This second edition substantially extends, updates and clarifies the previous edition.